2013
DOI: 10.12816/0004768
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge , Attitude and Practice of Parents Towards Childhood Vaccination

Abstract: Background: The prevention and treatment of hypertension are a high priority in medicine Background: It has been recently reported by WHO that a large proportion of children fail to complete their immunization schedule. System weaknesses, low public awareness, fears and misconceptions about vaccines were responsible for that. Despite nearly 100% vaccination rate in Saudi Arabia, often parents delay vaccination and do not fully understand the value of immunization, except that it is mandatory for birth certific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
14
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 16 publications
(22 citation statements)
references
References 21 publications
(20 reference statements)
3
14
1
Order By: Relevance
“…Most caregivers at this age had probably attended antenatal clinic services where a general health education on childhood immunizations is given or had immunized a child before. This is similar to a study conducted in Saudi Arabia which showed that older mothers were less likely to have knowledge and positive attitude towards child vaccination 18 . More females than males had good knowledge of pentavalent vaccine.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Most caregivers at this age had probably attended antenatal clinic services where a general health education on childhood immunizations is given or had immunized a child before. This is similar to a study conducted in Saudi Arabia which showed that older mothers were less likely to have knowledge and positive attitude towards child vaccination 18 . More females than males had good knowledge of pentavalent vaccine.…”
Section: Discussionsupporting
confidence: 89%
“…However, the results were similar to the findings of a study conducted in UAE in 2011 and Saudi Arabia in 2013. 17,18 Knowledge was particularly high among respondents within the age group of 25-34 years. Most caregivers at this age had probably attended antenatal clinic services where a general health education on childhood immunizations is given or had immunized a child before.…”
Section: Discussionmentioning
confidence: 92%
“…Knowledge and attitude of parents and sociocultural factors can influence the immunization status of children. 3 In this study, we have tried to explore these factors which could influence the immunization status of children.…”
Section: Discussionmentioning
confidence: 99%
“…2 According to the WHO, over 1.5 million children die from vaccine-preventable diseases globally and current immunization programs save more than 3.2 million lives each year and additional 1.7 million lives a year can be saved by full utilization of the existing vaccines. 3 By increasing immunization coverage to above 80%, disease transmission can be interrupted, whereby unimmunized children are also protected because of the herd immunity. 4 To achieve this goal a full course of potent vaccines should be given at the right time.…”
Section: Introductionmentioning
confidence: 99%
“…12 Similar results are obtained by EKOS research associates, Angelillo et al, Inamder et al, Zahrani JA and Mohammed A et al where parents (both mothers and fathers) with higher level of education had a better knowledge of vaccines. 2,3,7,13,14 In contrast, studies by Garrido C et al and Mapatano MA et al, showed that parental education does not influence the awareness regarding vaccination. 15,5 Study findings show a significant association between the parent's age (both fathers and mothers) and vaccination awareness among them.…”
mentioning
confidence: 91%